2021
DOI: 10.2147/dddt.s292642
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol Ameliorates Lung Inflammation and Airway Remodeling via Inhibiting the Abnormal Activation of the Wnt/β-Catenin Pathway in Chronic Asthmatic Mice

Abstract: Background Curcumol exhibits anti-inflammatory effect, but its effect on chronic asthma lacked research. Therefore, this study explored the role of curcumol in asthma. Methods A chronic asthmatic mice model was established by ovalbumin induction. After treatment with curcumol, airway resistance in mice was detected by forced oscillation technique. The histopathological features of airway tissues, pulmonary inflammation, and inflammation cell recruitment in the bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…17,21-24 Importantly, Jia et al have demonstrated that curcumol helps in treating airway remodeling and lung inflammation in chronic asthmatic mice. 25 However, the in vitro experimental effect of curcumol on asthma has not been studied. Therefore, this study detected the effect of curcumol on PDGF-BB-stimulated ASMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,21-24 Importantly, Jia et al have demonstrated that curcumol helps in treating airway remodeling and lung inflammation in chronic asthmatic mice. 25 However, the in vitro experimental effect of curcumol on asthma has not been studied. Therefore, this study detected the effect of curcumol on PDGF-BB-stimulated ASMCs.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, curcumol has been proved to ameliorate airway remodeling and lung inflammation in a mouse model of chronic asthma (8). 25 However, the molecular mechanisms of curcumol in asthma are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma, featured by airway inflammation, is inseparable from inflammation and immune disorders. Jia et al found that curcumol improved pneumonia and airway remodeling in mice with chronic asthma by inhibiting the Wnt/ β -catenin pathway through experimental studies [ 37 ]. Lyu et al found that Pinellia ternata reduced the allergic response to asthma in mice by inhibiting the activation of TH2 cells and the expression of the inflammatory factor IL-4 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study by Li et al showed that curcumol suppresses proliferation of the LUAD cells, A549 and H460, by arresting the cell cycle, altering the expression of apoptosis signaling pathways and inducing tumor cell apoptosis ( 14 ). In chronic asthmatic mice, curcumol was found to reduce pulmonary inflammation and airway remodeling by decreasing cytokine levels ( 15 ). In addition, curcumol was reported to inhibit LUAD growth and metastasis and overcome tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) resistance in lung cancer ( 16 ).…”
Section: Introductionmentioning
confidence: 99%